2018
DOI: 10.5539/ies.v11n4p74
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Using the Differentiated Instruction Strategy: A Case Study in the General Education Stages in Saudi Arabia

Abstract: The study identifies the most important challenges facing general education male and female teachers in applying the differentiated instruction strategy in different stages of education in the Eastern Province in the Kingdom of Saudi Arabia. To achieve this, the researcher designed a questionnaire consisting of 47 paragraphs on five axes. It was distributed to 275 male and female teachers in Dammam city, after having verified its validity and stability,The results indicate that the degree of the challenge of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…The current study also showed that even experienced virtual schools may be effective in one area of differentiated instruction yet fail to deliver in others. Other research has shown that obstacles to differentiation may be technological, instructional, administrative, and organizational in nature (Aldossari 2018 ; Doubet 2007 ). Future research should investigate what kind of obstacles may be hindering application of differentiated instruction in the areas of assessment, curriculum, and strategies, as well as considering potential solutions to overcome these obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…The current study also showed that even experienced virtual schools may be effective in one area of differentiated instruction yet fail to deliver in others. Other research has shown that obstacles to differentiation may be technological, instructional, administrative, and organizational in nature (Aldossari 2018 ; Doubet 2007 ). Future research should investigate what kind of obstacles may be hindering application of differentiated instruction in the areas of assessment, curriculum, and strategies, as well as considering potential solutions to overcome these obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Siam and Al-Natour (2016) followed the mixed approach by collecting data using surveys and interviews, while the study of Hobson (2008) used surveys and observations. In general, the majority of those studies (Affholder, 2003;Al-Bultan, 2017;Aldossari, 2018;Good, 2006;Netterville, 2002) agreed with the current study on adopting the descriptive approach using the survey as the main tool for data collection. On the other hand, several other studies (Abanmi, 2018;Abdul Al-Qader, 2019;Abdul Al-Bar, 2018;Al-Rushoud & Nofal, 2017;Al-Ghamdi, 2018;Bayoumi & Al-Jundi, 2018;Halisi & Sharif, 2012) differed from the current study by following the experimental or quasi-experimental approach.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Among the most prominent obstacles teachers face, Siam and Al-Notour (2016) reported poor administrative support, poor parent support, time constraints and lack of educational resources. In a study carried out by Aldossari (2018) to identify the most important obstacles and challenges facing teachers of public education while applying differentiated instruction, the results indicated that the student individual differences ranked first, followed by challenges related to the school environment, the nature of differentiated instruction, teacher challenges and, finally, challenges related to training.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations